2018
DOI: 10.1002/lary.27750
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spin in the abstracts of otolaryngology randomized controlled trials

Abstract: Objective Spin, the misrepresentation and distortion of research findings, has been shown to affect clinical decision making. Spin has been found in randomized controlled trials (RCTs) published in various fields of medicine, but no study has tested for the presence of spin in otolaryngology RCTs. The purpose of this study is to evaluate the abstracts of RCTs found in the otolaryngology literature for spin. Methods In this cross‐sectional analysis, we analyzed the abstracts of RCTs for spin using a pilot‐teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 19 publications
7
40
1
Order By: Relevance
“…Our results agreed with other studies in the medical literature that investigated spin strategies and misrepresentation of RCT results with various methodologies [4,5,[51][52][53][54]. Austin et al [5] reported some form of spin to exist in 47% of the included RCT abstracts while Cooper et al [53] reported spin to be as high as 70% of the included articles.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results agreed with other studies in the medical literature that investigated spin strategies and misrepresentation of RCT results with various methodologies [4,5,[51][52][53][54]. Austin et al [5] reported some form of spin to exist in 47% of the included RCT abstracts while Cooper et al [53] reported spin to be as high as 70% of the included articles.…”
Section: Discussionsupporting
confidence: 90%
“…Our results agreed with other studies in the medical literature that investigated spin strategies and misrepresentation of RCT results with various methodologies [4,5,[51][52][53][54]. Austin et al [5] reported some form of spin to exist in 47% of the included RCT abstracts while Cooper et al [53] reported spin to be as high as 70% of the included articles. Interestingly, Pitkin et al [8] compared data reported in the abstract of a random sample of RCTs published in 6 major medical journals to the data presented in the full-text manuscripts and found that inconsistencies at variable levels (18%-68%) existed between data reported in the abstract compared to the full text.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We compared the prevalence of spin in spin studies with historical data on spin prevalence calculated in our previous systematic review 2. However, recent studies of spin suggest that the prevalence of spin has remained stable over the past two years 34567. Different study designs are prone to different biases.…”
Section: Discussionmentioning
confidence: 99%
“…Spin in scientific papers refers to practices that distort the interpretation of results and mislead readers to view the results in a more favourable light 1. Identification and characterisation of spin is an active area of research with a systematic review of spin studies published in 20172 and additional recent studies 34567. The findings of these studies suggest that the prevalence of spin is high across a variety of research fields and that interventions to reduce spin are needed.…”
Section: Introductionmentioning
confidence: 99%